Association between surgical repair of aortic aneurysms and the diagnosis of subsequent cardiovascular diseases. Issue 6 (June 2020) - Wang, Jen-Chun; Chien, Wu-Chien; Chung, Chi-Hsiang; Lin, Chih-Yuan; Hsu, Chin-Wang; Lin, Chin-Sheng; Tsai, Shih-Hung
Highlights: Open surgical repair (OSR) of aortic aneurysms (AAs) could be associated with fewer subsequent cardiovascular disease events. OSR of AAs could be associated with fewer incidents of subsequent acute myocardial infarction. The advantage of OSR might be taken into consideration when treating AAs. Abstract: Background: Cardiovascular diseases (CVDs) and aortic aneurysms (AAs) share several clinical risk factors. However, the potential effects on future CVDs of surgical treatments involving the open surgical repair (OSR) of AAs are unknown. We hypothesize that the OSR of AAs is associated with subsequent CVDs. Methods: The data for this nationwide population-based retrospective cohort study were obtained from the National Health Insurance Research Database in Taiwan. The outcome assessed in this study was the cumulative incidence of CVDs in patients with AAs during a 14-year follow-up period, which was further stratified according to those who underwent OSR, endovascular aneurysm repair (EVAR), and nonsurgical treatment (NST). Results: Our analysis included 11, 764 patients with AAs, of whom 2, 524 received surgery and 2, 524 were propensity score-matched controls. Compared to the controls, patients who received OSR exhibited a significantly decreased incidence of CVD development [adjusted hazard ratio (HR) = 0.89, p  = 0.006]. Furthermore, compared to patients who received NST, patients who received OSR had a significantly lower incidence of subsequent acute myocardial infarction (adjusted HR = 0.793, p  = 0.037). Conclusions: Compared to NST, OSR of AAs could be associated with a lower incidence of subsequent CVDs.